Synchronized Pedaling with Martial Arts Improves Quality of Life of Women with Breast Cancer - Navarro-Sanz, Ana; Espejo-Reina, Alejandro; Cerezo-Guzman, Maria Victoria; Fernandez-Ortega, Juan F.; Meza-Leiva, Hector; Conejo-Tirado, Inmaculada; Santiago-Sanchez, Clara (International Journal of Sports Medicine, 2018)
Physical exercise improves the physical condition of women who have been undergone surgery for breast cancer. This study evaluated the effect of a new martial arts program that combined aerobic endurance and muscle strength exercises on improving upper limb function and aerobic performance of women who have undergone breast cancer surgery. Fifty-three women who had previously undergone breast cancer surgery with axillary lymph node dissection, radiotherapy and/or chemotherapy participated in the twelve-week program. Participants were randomly assigned to two groups; a study group (28 participants) in which participants carried out a synchronized pedaling with martial arts routine of 2 sessions per week, and a control group (22 participants) who received usual care. Study group participants demonstrated a significant increase in right hand and quadriceps strength, maximum oxygen consumption, max power-to-weight ratio, muscle mass percentage and a decrease in fat mass percentage (p≤0.05). A controlled training system like synchronized pedaling with martial arts, which combines aerobic and strength exercises, appears suitable for improving the muscle strength and aerobic capacity of these breast cancer participants.
Keywords: exercise program; physical activity; mastectomy; axillary dissection; chemotherapy; lymphedema